Synthesis and tribological characterization of copper based composites containing carbide - Tyagi R.; Singh Gautam R.K. (My University, 2025)
Keeping in view the importance of the Cu based composites in sliding electric contact applications, the aim of the study is synthesise copper-chromium alloy based composites containing different wt. % of TiC by using a cost effective stir casting technique and to compare their mechanical and tribological behaviour. The study also proposes to analyse the friction and wear behaviour of the formed composites under the sliding speed of 1m/s and load varied 5 N, 10 N, 15 N and 20 N. The hardness of the composite Cu-1wt%Cr-1wt%TiC and Cu-1wt%Cr-2wt%TiC has been found to increase slightly when compared with Cu-Cr alloy and as received Cu. The wear rate was found to show linear trend with increasing normal load following the Archard law. However, composites were found to show low wear as compared to that observed in pure copper. This might be due to high hardness of the composite, the compact transfer layer of wear debris and due to presence of hard TiC particles whicg results in a lower real area of contact which further causes lower wear. There was found no cracks in the composite. The addition of chromium was found to increase the wettability and mechanical properties. The composite hardness and strength was found to increase with addition of TiC and chromium element in the matrix phase up to certain content. © 2020 IOP Publishing Ltd. All rights reserved.